Explaining Strategies for Developing Clean Transportation in the Central Area of Cities (Case Study: District Eight of Shiraz) - Tani, Majid; Peyvastehgar, Yaghowb; kholghifard, Mehrdad; Zolfegharifar, Sayyed Yaghoub (Management Strategies and Engineering Sciences, 2023)
The metropolises of developing countries have consistently struggled with traffic and its associated problems, leading to significant losses. Considering the importance of this issue, the present study aims to explain strategies for developing clean transportation in District Eight of Shiraz. This study employed mixed methods (descriptive-analytical and survey). In other words, data collection utilized both field methods (questionnaire completion and expert interviews) and library research. Furthermore, to achieve the research objectives, the SWOT model and the QSPM matrix were applied. The study's findings indicate that the superior strategy for developing clean transportation in District Eight of Shiraz is the ST strategy. In other words, for the development of clean transportation, the studied area should adopt a defensive (ST) strategy as its operational foundation. Regarding the development of clean transportation in the studied area, the top operational strategy priority should be providing diverse transportation plans for public use.